2012
DOI: 10.6061/clinics/2012(06)02
|View full text |Cite
|
Sign up to set email alerts
|

Early interdisciplinary hospital intervention for elderly patients with hip fractures – functional outcome and mortality

Abstract: OBJECTIVES:Hip fractures are associated with high levels of co-morbidity and mortality. Orthogeriatric units have been shown to be effective with respect to functional recovery and mortality reduction. The aim of this study is to document the natural history of early multidisciplinary intervention in elderly patients with hip fractures and to establish the prognostic factors of mortality and walking ability after discharge.METHODS:This observational, retrospective study was performed in an orthogeriatric care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 47 publications
4
61
1
7
Order By: Relevance
“…Moreover, in a study conducted in the city of Niterói (RJ), it was observed that 78.2% of the fractures in the elderly had occurred in lower limbs (12) . Although these data indicate a higher risk for certain groups, falls in the elderly and resulting fractures are common events around the world, associated with significant mortality and variations as to consequences (13) . This may be related to presence of comorbidities, longer hospitalization time, and complications arising from surgical procedures, such as general anesthesia (14) .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a study conducted in the city of Niterói (RJ), it was observed that 78.2% of the fractures in the elderly had occurred in lower limbs (12) . Although these data indicate a higher risk for certain groups, falls in the elderly and resulting fractures are common events around the world, associated with significant mortality and variations as to consequences (13) . This may be related to presence of comorbidities, longer hospitalization time, and complications arising from surgical procedures, such as general anesthesia (14) .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The main goal of rehabilitation in geriatric population after the hip fracture is achievement and maintaining pre-fracture level of functional independence in movement and every day activities. 3,4 For this purpose different rehabilitation protocols are used for the treatment of these patients and there are efforts to identify specific factors that could point out whether rehabilitation goal is achievable and in what capacity. [5][6][7] It is known that improvement in functional independence is different for different patients, but however, we still lack the consensus concerning the factors that could be of great significance (age, gender, comorbidity, race, prefracture functional level, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Tim mora održavati redovne sastanke na kojima razmenjuje iskustva u radu sa pacijentom, zabeleženi napredak i diskutuje probleme. Rad rehabilitacionog tima mora podrazumevati i rad sa porodicom bolesnika, njihovo redovno informisanje o stanju pacijenta i daljim opcijama, kao i pripremu za resocijalizaciju bolesnika koja odgovara njemu ali i njegovom okruženju (87,88).…”
Section: Specifičnosti Lečenja I Rehabilitacije Gerijatrijske Populacijeunclassified
“…Poznato je da godine starosti predstavljaju jedan od glavnih faktora rizika za prelom kuka ali i negativni prediktivni faktor za oporavak nakon preloma kuka, kao i povećani mortalitet (86,87). U našem ispitivanom uzorku prosečne godine starosti ispitanika su bile 77,72 godine, a u praćenim grupama po vrsti rehabilitacionog tretmana, u grupi 1 koja je imala rehabilitacioni tretman koji uključuje i hidroterapiju prosečne gdine starosti su bile 74,80, dok su u grupi 2 koja nije imala rehabilitacioni tretman sa hidroterapijom, prosečna starost ispitanika bila 80.08 godina.Ovakva prosečna raspodela prema godinama starosti za celu grupu konzistentna je sa godinama starosti ipitanika u populaciji starijih u ostalim studijama (85,86,87,88). Upoređivanjem prosečne starosti pacijenata u dve posmatrane grupe nalazimo postojnje visoko statistički značajne razlike između grupe 1 i grupe 2 (Tabela br.3) što znači da su pacijenti uključeni u program bez hidroterapije bili značajno stariji od onih u grupi 1 uključenih u program koji podrazumeva i hidroterapiju.…”
Section: Diskusijaunclassified
See 1 more Smart Citation